AI-POWERED APPS TO ENHANCE NOVICE NEWSREADERS’ ENGLISH PRONUNCIATION (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2022)
Among the goals that Communication students, who are ESP learners, desire to achieve is to become professional newsreaders who can deliver the news in both Indonesian and English. These novice newsreaders with little to no knowledge about news delivery in English often face problems with English pronunciation. This study aims to help forty-one novice newsreaders, who are students of the Islamic Broadcasting and Communication Department, with their English pronunciation using AI-powered apps and to reveal their perceptions of the apps. The students were involved in one cycle of Classroom Action Research (CAR), where they had to make a video of them reading English news before using the apps as the pre-test and another video after the lecturer taught them how to use the apps as the post-test. The researcher distributed a questionnaire via Google Form after the post-test to complete the data. The results show that AI-powered apps can enhance novice newsreaders’ English pronunciation, especially in the aspects of Accuracy, Key Words, Chunking and Pausing, Intonation, as well as Sounds and Vocal Features; yet, Intonation becomes the lowest improved aspect. Also, the respondents believed that the apps help them with their future job as newsreaders, are easy to use, and give instant feedbacks, which are necessary for independent learning and suitable for ESP learners. The ELSA app rose to the top of the list of the respondents’ favorites. Finally, it is recommended that future researchers carry out comparable studies that focus on one or two particular English sounds evaluated across multiple cycles.